Groping environmental sensitivity as an antecedent of environmental behavioural intentions through perceived environmental responsibility. Issue 2 (13th January 2021) - Singh, Sandeep; Sharma, Priyanka; Garg, Nameeta; Bala, Rajni
Abstract : Purpose: This paper aims to study the mediating role of perceived environmental responsibility on the relationship between environmental sensitivity and pro-environmental behavioural intentions. Design/methodology/approach: The sample of the study was 256 respondents. The snowball sampling technique was applied to reach the maximum number of respondents. The data was collected with three standardized scales. It was conducted on the general mass in the northern region of India. The hypotheses were tested by applying partial least square structural equation modelling (PLS-SEM). Findings: The study exhibits a significant positive effect of environmental sensitivity (ES) on environmental responsibility (ER) and environmental behavioural intentions (EBI). Environmental responsibility has a significant positive effect on environmental behavioural intentions. As expected, environmental responsibility partially mediates the relationship between environmental sensitivity and environmental behaviour intentions. Research limitations/implications: The study has tested the theory-driven hypotheses and confirmed the indirect effect of environmental sensitivity on environmental behavioural intentions. The sample of the study is mixed with various units such as students and professionals. The sample was not represented in any particular section of society. The responses of the respondents were measured at a five-point Likert scale. For better results, the seven-point Likert scale can be better. The study can be replicated in another region of India. Multi-group analysis can be a better scope of research in the future. The model can be compared based on demographic information, region, etc. Practical implications: The government can rectify or make various policies on environmental protection based on the findings. The results can be useful for identifying training needs for the general mass. The study suggests that the government can organize various seminars on specific issues at the general platform. Overall, the study is also useful in policymaking and implementation regarding environmental protection. Originality/value: As per the best of our knowledge, this is the first study exploring a causal link between environmental sensitivity, environmental responsibility and environmental protection conducted in India. The observed mediation effect of the ES on the EBI through ER adds new knowledge on the topic. As per the methodology point of view, the latest guidelines regarding PLS-SEM and mediation are followed, which can be useful for research in the future. Overall, the findings of the study exhibit an important contribution to the academic, methodology and general mass.